Optimizing Employee Performance: The Role of Supervision and Work Discipline at PT Silver Kris Bandung - Siti Nur Aisyah; Muji Rahayu (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to determine the influence of supervision and work discipline on employee performance. The population of this study is employees of PT Silver Kris, a manufacturing company that produces yarn in the textile industry. The research method used is a quantitative approach with descriptive analysis. Sample calculation uses the Slovin formula. The sample was determined using random sampling techniques. Data was collected through the distribution of questionnaires. The data processing results show that both partially and simultaneously it is confirmed that supervision and work discipline have a positive and significant influence on performance The results of this study show that supervision and work discipline have an important role in improving the performance produced. High supervision and work discipline will result in high performance.